Analisis Pengembangan Ruang Terbuka Hijau dengan Prioritas Tertinggi untuk Mencegah Urban Heat Island pada Lanskap Kota Depok, Jawa Barat - Widyanti, Ramanda; Nasrullah, Nizar; Sulistyantara, Bambang (http://arl-faperta.ipb.ac.id/, 2025)
Depok is one of Jakarta’s satellite towns with density populations increasing throughout urbanization. The population growth rate of this city has gained by 1,92% in 2021 or an increase of 0,28% since 2020. As an impact of it, the transition of green open spaces (GOS) to built-up land could not be helped. The quantity of vegetation as the main material of GOS that can improve urban quality through evapotranspiration and pollutant reduction keeps dwindling. Therefore, analysis of GOS development priority was needed to prevent the diminish of the city’s ecological value based on Normalized Difference Vegetation Index (NDVI), Land Surface Temperature (LST) and density population’s intensity in 2021 by using Landsat 8 OLI-TIRS. According to the study, Sukmajaya is one of sub-districts with highest development priority of GOS, especially in business area due to the wide-scale of its GOS is only 3,26 km2 which has NDVI is 0,31 and also its surface temperature is 30,5ºC. Meanwhile, Sawangan and Bojongsari sub-districts are the lowest priority for GOS developments due to having more than 30% of vegetation area and their surface temperature are 28,7ºC and 28,8ºC. The output of this study is a recommendation that used as a reference by the government or any stakeholders to raise awareness of GOS necessary, so the quality of urban ecology could be raised and the health of residents would be achieved.